1992
DOI: 10.1007/bf01570076
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of exopolysaccharide production by enterohemorrhagicEscherichia coli

Abstract: Enterohemorrhagic Escherichia coli O157:H7 produces visibly slimy colonies when grown on Sorbitol/MacConkey or Maloney's agar plates at room temperature, indicative of exopolysaccharide (EPS) production. Eighteen of 27 (67%) wild-type E. coli O157:H7 isolates produced enough EPS to be visually distinguishable. Of five strains that showed no visible EPS production on these media, four (80%) did produce slimy colonies on media containing higher salt concentrations. Measurements of EPS production by colorimetric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 27 publications
2
51
1
Order By: Relevance
“…Enteropathogenic strains of E. coli have been shown to be capable of elucidating mucoid capsule (Junkins and Doyle, 1992), although colanic acid capsule plays no apparent role in evasion from phagocytosis or resistance to complement-mediated killing (Allen et al, 1987). A thorough understanding of the mechanism of activation of the rcs signalling pathway would resolve the mystery of why E. coli possesses such a tightly regulated adaptive response.…”
Section: Discussionmentioning
confidence: 99%
“…Enteropathogenic strains of E. coli have been shown to be capable of elucidating mucoid capsule (Junkins and Doyle, 1992), although colanic acid capsule plays no apparent role in evasion from phagocytosis or resistance to complement-mediated killing (Allen et al, 1987). A thorough understanding of the mechanism of activation of the rcs signalling pathway would resolve the mystery of why E. coli possesses such a tightly regulated adaptive response.…”
Section: Discussionmentioning
confidence: 99%
“…The EPS matrices from different bacteria are composed of polysaccharides, including alginate in Pseudomonas aeruginosa when forming biofilm in cystic fibrosis patients (11), cellulose in Salmonella enterica serovar Enteritidis (30), and colanic acid in Escherichia coli (9). It has been suggested that most bacteria can produce EPS in specific environmental conditions, but production is typically lost by culture on bacteriological media in a laboratory setting (19). Thus, while bacterial species have genes that determine the amount and composition of the EPS produced, environmental surfaces and conditions are also important factors in EPS production and play a role where specific bacterial species can form biofilms (4,5).…”
mentioning
confidence: 99%
“…The ability of strains of G. polyisoprenivorans to produce smooth and rough variants was previously noted in strains VH2 (2,23) and Y2K (2). Fusconi and Godinho (14) selected this strain for EPS production studies on the basis of the mucoid aspect of colonies on solid media and the mucoid mode of growth in liquid media, characteristics that indicate production of large amounts of EPS by bacterial strains (8,18). Experimental measurement of EPS produced by Lc strain during growth on one out of the two carbon sources confirmed predictions of EPS production by the strain.…”
Section: Discussionmentioning
confidence: 87%